Drivers of Financial Inclusion and Effect of Covid-19 on Electronic Payments in West Africa - Paul Adjei Onyina (E-Journal of Humanities, Arts and Social Sciences)
This study examined the drivers of financial inclusion as well as how COVID-19 affected West Africa in terms of electronic payments. It used the World Bank’s Global Findex 2021 data collected at the time of the COVID-19 pandemic with 1000 respondents each from Senegal, Togo, Burkina Faso, Guinea, Mali, Sierra Leone, Nigeria, Ghana, Benin, Liberia and Cameroon and model logit regression to investigate the drivers of financial inclusion and how COVID-19 affected it. With regard to key drivers of financial inclusion, it found that female and lower income groups have low inclusion levels which decline when income increases; also, the more educated persons, are linked to high financial inclusion. On account ownership of mobile money, there is discrimination of financial inclusion based on sex. Distance from the office of a financial institution poses a key obstacle to financial inclusion for females and various income groups, but the cost is not a major worry. Informal financial practices are not very popular. The study found that highly educated persons used electronic payment systems to settle utility bills for the first time during the COVID-19 pandemic. The study recommends policies that lead people closer to financial services to reduce financial exclusion. Again, individuals should be stimulated to adopt electronic payment systems to help reduce financial exclusion. The originality of the study stems from the usage of figures provided by the World Bank’s Global Findex in 2021 which is unique in totality. This study adds to current knowledge by evaluating drivers of financial inclusion in West African countries by looking at current issues on finances focusing on the sub-region during the COVID-19 pandemic.